A Study on the Burnout Levels of Hospital Patient Services Employees - Çan, Özge; Çimen, Mesut; Özsarı, Haluk (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2017)
ABSTRACT Objective: Burnout is often seen in the service sector and in areas with stressful human interactions. In hospitals patient services employees are also one of the groups at risk of experiencing burnout syndrome due to the intense involvement of close personal relations. This study aimed to determine burnout levels of patient services employees in private hospitals. Method: The sample of this study included patient services employees from seven private hospitals located in Istanbul, Turkey. In January 2016, a survey study was conducted with research participants (n=295). The measurement scale used was Maslach’s Burnout Inventory. The burnout level was examined relating to age, gender, marital status, number of children, education, tenure, and monthly income. Findings: According to the survey results, there was a significant difference in burnout scores among people of different ages, genders, education levels, and monthly incomes. On the other hand, there was not a significant relationship between burnout levels and marital status, number of children or tenure in patient service personnel. Moreover, it was found that the burnout level of patient services employees is low. Specifically, the score of the depersonalization aspect of burnout was found to be minimal. Conclusion: It was concluded that burnout is an important issue that needs to be prevented and overcome with patient service employees.